Complications in patients with spinal cord injuries: a clinical study from a third level rehabilitation center in Turkey - Koca, Tuba Tülay; Koçyiğit, Burhan Fatih; Berk, Ejder; Nacitarhan, Vedat (The European Research Journal, 2019)
Objectives: Normal lifespan can be achieved by avoiding complications in patients with spinal cord injuries (SCIs). We aimed to characterize our spinal cord injured patients and to obtain necessary information to prevent complications. Methods: This retrospective, cross-sectional study included 44 patients with subacute/chronic SCIs, who were included in an inpatient rehabilitation program from 2012 to 2017. The patients’ epidemiological data, etiology, neurological examinations, complications, and accompaying conditions were analyzed. The neurological level, functional ambulatory scale (FAS), and American Spinal Cord Injury Association (ASIA) impairment scale were used for the classification of patients. Results: A total of 44 patients between 16 and 81 years of age (median: 35) were included in the study. Of these, 65.9% were male. The most common etiologies were falling down from a height (31.8%), spinal surgery (29.5%), and traffic accidents (15.9%) respectively. When we look the neurological status of these patients, FAS: 0 (38.6%) and ASIA: C (40.9%) were the most common cases seen in the population. Eighteen patients (40.9%) were wheelchair-bound. Urinary (34.1%), dermatologic (29.5%), and psychiatric (22.7%) complications were the most common in the patients. Patients with low FAS levels were young (in early period), and their spasticity, urinary incontinence, and urinary and dermatological pathologies were found to be high. The wheelchair-bound patients were mostly young, and they had significantly high urinary incontinence, urinary and dermatological pathologies. Conclusions. In our rehabilitation clinic, subacute/chronic SCI diagnosis is most commonly seen in young men, with thoracic vertebrae being the most common, followed by falling from a height. The most common complications were urinary and dermatological pathologies. The present study found higher rates of complications in patients with higher grades of injuries and in patients with lower functional levels.